The Changing Role of Blogs in Science Information Dissemination. - Laksamee Putnam (Issues in Science and Technology Librarianship)
In academia, research and publication are essential markers for indicating your expertise. However, the publication process can take a long time and today it is possible for information to be spread almost instantaneously. For scientists the ability to share research quickly increases cooperation and potentially makes their research stronger. There are numerous science blogs now available covering a wide range of topics including environment, medicine, life science and more. The blog entries are written by scientists all over the world and cover topics from mundane life to in-depth analysis of their current research. This paper will go over the blogs available to scientists today, how science blogs can contribute to the e-learning process for all audiences, and the pros and cons of reading and writing a science blog. Reprinted by permission of the publisher.